The Effect of Sacha Inchi Tempe on Blood Glucose, HOMA-IR, and TNF-ɑ in Rats with Metabolic Syndrome - Setyawati, Amalia Rani; Anjani, Gemala; Mahati, Endang; Afifah, Diana Nur; Syauqy, Ahmad; Astawan, Made; Rahmawati, Irma Sarita (Jurnal Gizi dan Pangan, 2024)
This research aimed to evaluate the impact of sacha inchi tempe (Plukenetia volubilis L.) on Fasting Blood Glucose (FBG), Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), and Tumor Necrosis Factor Alpha (TNF-ɑ) levels. In addition, metabolic syndrome was induced in 36 male Wistar rats aged 2 months at 150–200 g weight by giving a High-Fat High-Fructose diet (HFFD) for 2 weeks. The extract was administered through oral gavage in dose-dependent manner and rats were allocated into 6 groups, namely: 1). Normal control or K0; 2). Negative control or K-; 3). Positive control or K+ with 0.18 mg/200 g BB of simvastatin; 4). Intervention with 0.9 g sacha inchi tempe or P1; 5). Intervention with 1.8 g sacha inchi tempe or P2, and; 6). Intervention with 3.6 g sacha inchi tempe or P3. Meanwhile, normal chow rats were used and served as the control group. After 2 and 5 weeks of induction and intervention, blood was drawn to determine FBG. Blood insulin was examined after 5 week of intervention. Rats were euthanized at the end of the intervention for hepatic TNF-α analysis before calculating HOMA-IR. The result showed that there was a significant difference (p<0.05) in FBG, HOMA-IR and hepatic TNF-α levels after sacha inchi tempe treatment. Rats receiving the highest dose of sacha inchi tempe had the most significant reduction (p<0.05) in FBG, HOMA-IR and hepatic TNF-α, when compared to simvastatin group. Therefore, sacha inchi tempe could attenuate glycemic and inflammation profiles in metabolic syndrome.